Letter (copy) : Scottish food ship - Tewson, Vincent
030-0024-001 Secretary's HVT/FC/56. G.S. 17th October, 1938. Mr. D. Fernandez-Shaw, The Spanish Embassy, 21, Cavendish Square, W.1. Dear Sir, SCOTTISH FOOD SHIP. I am in receipt of your letter of the 12th instant and regret if there has been any mis-understanding in regard to the consignment of our goods for Spain. You will appreciate that we have been very concerned in regard to the Committee of Co-ordination for the Receipt of Goods, feeling satisfied that the close co-operation which existed between the Spanish Government and our International Solidarity Fund was quite satisfactory. I was under the impression from our conversation at Blackpool that for the time being it was understood that you would act as co-ordination officer in this country and that we were to forward to you particulars of all goods sent out. I also know that Mr. Schevenels, Joint Secretary of the International Solidarity Fund, has had certain conversations in regard to this matter, and it was he who sent particulars in regard to the manner in which the goods should be consigned. Probably the best course would be for us to have a talk together at an early date if you feel that the complications are such that this is necessary. Yours sincerely, Assistant Secretary. 292/946/30/24